People with Afro-Descendants in the Militias of the Northeast of New Spain. Century XVIII (Global Journal of Human-Social Science, 2024)
The military defense of the territories of the Hispanic Monarchy in the 18th century was always a central issue for the political class on both sides of the Atlantic The growing military needs derived from war contexts such as the Seven Years War 1757-1763 motivated - among other things - a growing incorporation of American populations into the defense of the territories including those of African descent This article analyzes the political and military implications of the enlistment of Afro-descendants in the militia corps of the Northeast of the viceroyalty of New Spain with special emphasis on the 18th century The writing is made up of three sections The first of them approaches the particularities of military defense in the northeast of New Spain during the Age of Enlightenment subsequently the general context of the militias in the Hispanic world is explained focusing of course on New Spain finally limiting ourselves to the participation of populations of African origin in that corps in the north of the viceroyalty The writing closes with a series of final reflections
Keywords: new spain; northeast; 18th century; afro-descendants